The Impact of Cultural Globalization on Sustainable Urban Development in Nigeria - Ezeudu, Tochukwu; Chukwudubem, Ezekwelu Kingsley (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
This study explores the intricate interplay between cultural globalization and sustainable urban development in Nigeria. Understanding the effects of cultural exchanges and interactions on urban dynamics is crucial in the context of rapid urbanization and global interconnectedness. The research employs a mixedmethods approach, combining qualitative interviews and quantitative surveys, to examine the multifaceted dimensions of this relationship. Findings reveal diverse manifestations of cultural globalization, including adopting global elements, hybridizing traditions, and emerging new cultural expressions within Nigerian urban contexts. These manifestations contribute to the formation of urban identities and influence community dynamics. Moreover, the study assesses the impact of cultural globalization on key dimensions of sustainable urban development, such as social inclusivity, environmental resilience, economic growth, and governance effectiveness. Challenges and opportunities arising from the collision of global and local cultures are explored. The study offers insights into policy implications, highlighting the need for inclusive governance, cultural preservation, and interdisciplinary collaborations. The results contribute to a nuanced understanding of cultural globalization's role in shaping urban sustainability, providing valuable guidance for policymakers and stakeholders striving to create vibrant and resilient cities.